PENGARUH PENERAPAN BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA PADA AGUNG TOYOTA AIR MOLEK - Windy Ariawan; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Purchasing decisions are an important part of the product marketing concept, this is the background of this research. Implementing the right marketing mix and good service quality in front of consumers are part of the factors supporting consumer purchasing decisions. This strategy is applied by Agung Toyota Air Molek. This study aims to determine the effect of Marketing Mix Implementation and service quality on purchasing decisions at Agung Toyota Air Molek. The method used in this research is descriptive and quantitative, with the data source of this research coming from primary data obtained through the interview process and distributing questionnaires which were then tested statistically through the SPSS program and secondary data using sales data of Agung Toyota Air Molek products starting in 2016-2020. The analytical method used in this research is simple and multiple regression analysis, and through validity and reliability tests. In this study the results obtained are that the marketing mix (X1) has a positive and significant effect on purchasing decisions (Y), service quality (X2) has a positive and significant effect on purchasing decisions (Y), and the marketing mix (X1) and service quality ( X2) has a positive and significant effect on Purchase Decision (Y) at Agung Toyota Air Molek. Keywords: Marketing Mix, Service Quality and Purchase Decision.